Brat Farrar - Tey, Josephine (Oxford : Oxford University Press, 2008)
You look exactly like him! You can take the dead boy's place and no one will ever know the difference. You'll be rich for life. And so the plan was born. At first Bratt Farrar fought against the idea, it was criminal, it was dangerous. But in the end he was persuaded, and a few weeks later Patrick Ashby came back from the dead and went home to inherit the family house and fortune. The Ashby Family seemed happy to welcome Patrick home, but Brat soon realized that somewhere there was a time-bomb ticking away, waiting to explode ...
Stage 5.
Keywords: Readers; Stage books